KANAK IMAGINARIES: A SENSE OF PLACE IN THE WORK OF DÉWÉ GÖRÖDÉ (Revue D’études Interculturelles De L’image, 2014)
The study of the Kanak imaginary in the work of the first published Kanak (indigenous) New Caledonian writer shows this to be permeated by a sense of place. Rootedness in, and intense community with the land is not incompatible with the fluidity of ancestral criss-crossing of the Pacific or of constant border-crossing(pathways of exchange between groups) but nonetheless remains central. The ‘hinterland’ constituted by the places of the tribu (customary lands) sets up a challenge to the dominance ofNouméa la blanche and Déwé Görödé’s articulation of places of identity re-negotiate the urban/regional or Noumea/Bush/Tribu nexus to counterbalance or contest national (French) imaginaries. Yet Görödé’s work presents both a return to a Kanak Place to Stand and a critical self in process (the latter situated in a ‘no man’s land’). The places in her work are ultimately ‘cognitively dissonant’: the marginal or hinter-land of Kanak imaginaries (the tribu), can hold (to) their own both outside and inside the city yet also open themselves up internally to multiplicity and critique.